Communication inside the LRA: Militarization of Acoli Language, a Cultural Patriotism or mere Rebel Indoctrination? - Ojok, James Onono; Abonga, Ajok Beatrice; Owor, Arthur (East African Nature and Science Organization, 2024)
In an ideal situation, there should be no positive effect of the LRA war in Northern Uganda, but what of the real testimonies that the LRA war brought in many development partners with school fees scholarships through institutions like Acoli Education Initiatives, Invisible Children, Windle Trust Uganda among others. But where are they going to pay for school, the northern children in ‘war affected areas’, and others up to universities, if it were not because of the devastating effect of the war on Education? This is still without the many successful grants and PhD projects completed within Uganda and around the globe based on LRA attachment to spirituality, transitional justice or interrogating the Acoli traditional justice system versus international laws. A debate can be constructed, if necessary, that the authorities on the LRA scholarships are from the global north -meaning the war pulled scholars from their comfort zones. Secondarily, what do we owe this to? For lack of a better word, other scholars would call it the ‘unintended’ positive effect of the war. This journal paper borrows the philosophy that if you are telling a story, it should be told up-side-down. Chimamanda Ngozi, the Nigerian writer, baptised it as a one-sided story and called it the danger of a single story (Adichie 2009). Schulz, Apio et al (2024) tell us about the ‘Love and Care in the LRA’, which this paper calls bravery, with all the horror stories of the LRA! This paper is grounded in some of these philosophies of Adichie (2009) and Schulz, Apio et al. (2024) of telling all sides of the story, attempting to reconstruct the LRA use of Acoli language throughout their military operations as a demonstration of Acoli cultural attachment, loyalty and depiction of Acoli cultural patriotism or activism argued by this paper. This was through using secondary data review and holding in-depth purposive interviews with four former LRA returnees plus two cultural chiefs, including extracting the archival journalistic records of the first author, who was an active journalist in northern Uganda for over 10 years between 2010 and 2021. This journal paper, however, does not underscore the pain and sufferings, the LRA brought on the people of Uganda and other neighbouring countries. However, this paper just gives an ontological side of the LRA, which is hard to find in terms of their particular role in promoting Acoli culture by using Acoli language as their military operational medium of communication